SPESIES COMPOSITION AND ABUNDANCE OF MARINE PHYTOPLANKTON OF DARUL AMAN WATER - Putra, Ira; Siregar, Sofyan Husein; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in Februari 2015 and was located at DarulAman waters. Samples were analyzed in the Biology Laboratory of Marine Science Department of Fisheries and Marine Science Faculty of Riau University. The aim of this study was to observe the phytoplankton communities. This research used survey method. The study found 25 species of phytoplankton, Compriting ofwere 16 species from Bacillariophyceae, 7 species from Dinophyceae, and 2 species from Cyanophyceae. Phytoplankton dominatingthe population was from group of Bacillariophyceae (Diatoms) 61%. The other groups comprising of Dinophyceae 29%, and Cyanophyceae 10%. Phytoplankton abundance varied from 266-339 ind/l, the higest value was in station 1 and the lowest value was in station 2. Phytoplankton community was dominated by the group of diatoms, such as Nitzschia sigma, Synnedra ulna, and Thallasiothrix delicatula.Keywords: Marine Phytoplankton, Bacillariophyceae, Marine of Riau